2022
DOI: 10.1021/acs.langmuir.2c02821
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Mechanism of Amidoxime Collector on the Flotation of Lepidolite: Experiment and DFT Calculation

Abstract: Lepidolite is an important mineral resource of lithium. With the increase in awareness of low-carbon and green travel, the demand for lithium has increased dramatically. Therefore, how to increase the output of lithium has to turn into high precedence. In this paper, amidoxime (DPA) was synthesized and used for the efficient collection of lepidolite. Dodecylamine (DA), a commonly used collector of lepidolite ore, was used for comparison. The collecting performances of DA and DPA for lepidolite were studied by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Lepidolite is another crucial mineral resource of lithium, for which a few quantum chemical studies of flotation reagents are available. For example, Huang et al [250] synthesized amidoxime as a collector for the efficient collection of lepidolite and compared it with a commonly used collector, DDA, to understand the collecting performances and adsorption mechanism of amidoxime using experimental and computational methods. The results suggested that amidoxime is adsorbed on the lepidolite surface via electrostatic attraction through the −CH 2 NH(CH 2 ) 2 C(NOH)N + H 3 group as the adsorption site.…”
Section: Other Minerals 81 Lithium-bearing Mineralsmentioning
confidence: 99%
“…Lepidolite is another crucial mineral resource of lithium, for which a few quantum chemical studies of flotation reagents are available. For example, Huang et al [250] synthesized amidoxime as a collector for the efficient collection of lepidolite and compared it with a commonly used collector, DDA, to understand the collecting performances and adsorption mechanism of amidoxime using experimental and computational methods. The results suggested that amidoxime is adsorbed on the lepidolite surface via electrostatic attraction through the −CH 2 NH(CH 2 ) 2 C(NOH)N + H 3 group as the adsorption site.…”
Section: Other Minerals 81 Lithium-bearing Mineralsmentioning
confidence: 99%
“…As a well-established method in quantum chemistry, density functional theory (DFT) has been used to obtain insights into the microscopic mechanisms of pollutant–material interfaces. HCHO-molecularly imprinted polymers have been designed and synthesized for HCHO removal with the assistance of DFT calculations . Both experimental studies and DFT calculations have been conducted to identify the adsorption behavior of HCHO on resin-based carbons and amine-modified diatomite. , The integration of experimental and DFT methods has emerged as a crucial strategy to identify the fundamental mechanisms involved.…”
Section: Introductionmentioning
confidence: 99%